PEMANFAATAN MEDIA BELAJAR VIDEO ANIMASI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Dwiana Amanatul Khasanah; Sri Jumini; M Yusuf Amin Nugroho (JOURNAL SAINS STUDENT RESEARCH, 2025)
Dwiana Amanatul Khasanah. UTILIZATION OF ANIMATED VIDEO LEARNING MEDIA TO INCREASE STUDENT LEARNING MOTIVATION IN PAI SUBJECT CLASS XI AT SMK TAKHASUS AL-QUR'AN WONOSOBO. Thesis, Wonosobo: Faculty of Tarbiyah and Teacher Training, Al-Qur'an Science University of Central Java in Wonosobo, 2025. The objectives of this study are: (1) to explore the concept of utilizing learning media to improve students' learning motivation in Islamic Religious Education (PAI) at SMK Takhasus Al-Qur’an, (2) to examine the implementation of animated video learning media for 11th-grade students at SMK Takhasus Al-Qur’an Wonosobo, and (3) to investigate the improvement in learning motivation through the use of animated video learning media in Islamic Religious Education (PAI) for 11th-grade students at SMK Takhasus Al-Qur’an Wonosobo. This study employed a quantitative quasi-experimental method, using tests, questionnaires, and documentation as research instruments.The results of the study show that: (1) the concept of utilizing learning media as a primary step in teaching indicates that animated video learning media offers effective and concrete steps to foster and enhance students’ motivation and learning outcomes in PAI subjects. (2) The implementation of learning media in the experimental class using animated video provided an attractive and unlimited space for students to gain experiences that facilitate better understanding of the taught materials. The learning media or the methods used in delivering the subject matter significantly influence students' comprehension. (3) The improvement of learning motivation through the use of animated video learning media in Islamic Religious Education for 11th-grade students at SMK Takhasus Al-Qur’an Wonosobo is proven by the learning outcomes, where the experimental class achieved an N-Gain score of 58.7%, compared to 30% in the control class. The increase in students' learning motivation was evidenced by an N-Gain score of 73% in the experimental class and 36% in the control class. The application of animated video learning media in PAI subjects is quite effective in enhancing students’ learning motivation, particularly on the topic of "Living in Peace with Tolerance and Avoiding Acts of Violence."